2020
DOI: 10.1186/s13550-020-00637-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted beta therapy of prostate cancer with 177Lu-labelled Miltuximab® antibody against glypican-1 (GPC-1)

Abstract: Purpose: Chimeric antibody Miltuximab®, a human IgG1 engineered from the parent antibody MIL-38, is in clinical development for solid tumour therapy. Miltuximab® targets glypican-1 (GPC-1), a cell surface protein involved in tumour growth, which is overexpressed in solid tumours, including prostate cancer (PCa). This study investigated the potential of 89 Zr-labelled Miltuximab® as an imaging agent, and 177 Lu-labelled Miltuximab® as a targeted beta therapy, in a mouse xenograft model of human prostate cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In addition to its potential diagnostic value, GPC1 has been evaluated as a potential target for antibody-based strategies, including anti-GPC1 mAb (11,88), antibodydrug conjugates (ADC) (89,90), CAR-T cell therapy (88,91), radiotherapy (92), photoimmunotherapy (93), and bispecific T cell engager (BiTE) (94) in preclinical settings (Table 2).…”
Section: Gpc1 As a Therapeutic Targetmentioning
confidence: 99%
“…In addition to its potential diagnostic value, GPC1 has been evaluated as a potential target for antibody-based strategies, including anti-GPC1 mAb (11,88), antibodydrug conjugates (ADC) (89,90), CAR-T cell therapy (88,91), radiotherapy (92), photoimmunotherapy (93), and bispecific T cell engager (BiTE) (94) in preclinical settings (Table 2).…”
Section: Gpc1 As a Therapeutic Targetmentioning
confidence: 99%
“…Importantly, the treatment was well tolerated with no adverse safety signals, which included assessment of organ histopathology. 117 Rationale for the targeting of GPC-1 for the delivery of therapeutic radiolabel is supported The use of alpha-emitters such as 213 Bi and Actinium-225 ( 225 Ac) as a component of targeted therapy has shown great promise both preclinically and clinically. 121 In prostate cancer (with metastatic bone disease), for example, the United States Food and Drug Administration (FDA) in 2018 approved the use of the first alpha-emitter, Radium 223 ( 223 Ra).…”
Section: Gpc-1 Directed Therapies In Solid Tumorsmentioning
confidence: 99%
“…Preclinical studies have demonstrated the utility of GPC-1 as an RIT target for the imaging and therapy of prostate tumors. 117 Miltuximab® radiolabeled with 89 Zirconium via a DFO chelate was used for the PET visualization of DU-145 tumor xenografts in mice. The study demonstrated specific accumulation and retention of the antibody in the tumor out to 7 days, which was the experimental endpoint, as well as expected clearance in normal organs including the liver.…”
Section: Gpc-1 As a Radioimmunotherapy Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…GPC-1 is a heparan sulfate proteoglycan (HSPGs) that is not expressed in normal adult tissues but is overexpressed in a range of tumours (39) . Pre-clinical studies have demonstrated potential for Miltuximab® as a radioimmunotherapy for solid tumours (40). We undertook the study to assess the safety, tolerability and biodistribution of gallium-67-labelled Miltuximab in patients with advanced solid tumours.…”
Section: Example Using Gallium-67 As Part Of a Theranostic Approachmentioning
confidence: 99%